PEMENUHAN HAK REHABILITASI ANAK KORBAN TINDAK PIDANA PENCABULAN DALAM PUTUSAN NOMOR 130/PID.SUS/2023/ PN.SITUBONDO: Fulfillment Of Rehabilitation Rights For Child Victims In Decision Number 130/Pid.Sus/ 2023/Pn. Situbondo - Ajeng Tiara Damayanti; Maria Silvya E. Wangga (Faculty of Law, Universitas Trisakti, 2025)
The crime of child sexual abuse as stated in Decision No. 130/Pid.Sus/2023/PN.Situbondo was committed by the victim's biological uncle, which resulted in the victim experiencing psychological trauma. As part of the recovery process, child victims have the right to obtain proper rehabilitation services, including the fulfillment of the rights of child victims of sexual abuse as stipulated in the decision. This research examines the formulation of the problem of how the fulfillment of rehabilitation rights for child victims in the case, as well as identifying the forms of rights that should be received by child victims as part of recovery. The methodology used is a normative approach with a descriptive-analytical nature, and the conclusions in this research are obtained through a deductive approach. Based on the results of the research, it was found that child victims did not receive medical or social rehabilitation, because the judge in his verdict did not consider the provisions of Article 2 of Presidential Regulation No. 75 of 2020. The rights of child victims are only partially fulfilled, while a number of other important rights have not been fully realized.